[PP.34.28]: ADHERENCE TO MEDITERRANEAN DIET IN PATIENTS WITH ACUTE ISCHEMIC STROKE. (June 2015) - Tuttolomondo>, A.>; Di Raimondo, D.; Casuccio, A.; Butta', C.; Pecoraro, R.; Clemente, G.; Corte, V. Della; Maida, C.; Simonetta, I.; Miceli, G.; Cirrincione, A.; Pinto, A.
Abstract : Objective: Mediterranean Diet that is characterized by a high intake of fruit and nuts, vegetables, legumes, cereals, fish and seafood; a low intake of dairy products, meat and meat products; and a moderate ethanol intake mainly in the form of wine and during meals, has become the standard for healthy eating. We conducted a retrospective study to evaluate the association between Mediterranean Diet adherence evaluated by means the calculation of Mediterranean Diet Score (MDS), stroke subtype and severity indexes and outcome of ischemic stroke. Design and method: The primary outcome in this study was differences in mean Mediterranean diet score between patients with acute ischemic stroke and subjects without acute ischemic stroke; Secondary outcomes were evaluation of a relationship between TOAST subtypes of ischemic stroke and mean Mediterranean Diet Score and between severity indexes of acute ischemic stroke and mean Mediterranean diet score. The type of acute ischemic stroke was classified according to the TOAST classification. We administered to all patients admitted with acute ischemic stroke or to their relatives a a 137-item validated food-frequency questionnaire (17) adapted to Sicilian population. A scale indicating the degree of adherence to the traditional Mediterranean diet was constructed by Trichopoulou et al Results: We enrolled 198 subjects with acute ischemic stroke and 100 control subjects without acute ischemic stroke. Among stroke patients we observed a significant correlation between MED diet score and female sex (R: 0.165; p = 0.023), atrial fibrillation (R: 0.152; p = 0.037), and SSS score (R: 0.306; P < 0.0005) whereas we observed a negative relationship between med diet score and CAD (R: -0.146; p = 0.045), NIHSS (R: -0.296; p < 0.0005) and Rankin scores (R:-0.229; p < 0.0005). Among stroke patients, lacunar subtype showed a higher mean Mediterranean diet (5.41 ± 1.51) score compared to LAAS subtype (3.59 ± 1.41) but not compared to cardioembolic (5.98 ± 1.83). Conclusions: We reported that patients with lower adherence to a Mediterranean Diet profile are more likely to have an atherosclerotic (LAAS) subtype of stroke, a worse clinical presentation of ischemic stroke with a higher mean NIHSS and a dependency with higher rankin score at admission.